Performance Analysis of a 2-Liter Solar Cooker with Comparison of Aluminum and Stainless Steel Containers - Perangin angin, siwan edi amanta; Napitupulu, Richard (Jurnal Polimesin, 2024)
The utilization of solar energy can be applied to household needs, such as using electric stoves. Solar panels serve as a tool for converting heat into electricity, which is then used to power solar cookers as a substitute for LPG-powered stoves. This study was conducted at the Faculty of Engineering, HKBP Nommensen University, located at Jl. Sutomo No.4A Medan, North Sumatra. The objective of the study is to compare the performance of a solar cooker PV DC system with an aluminium cooking container to a Solar Cooker with a stainless steel cooking container, focusing on differences in the rate of temperature increase. The test results show that aluminium containers are better at conducting heat than stainless steel. For instance, when cooking 2 liters of water, the temperature increase rate in an aluminum container is 1.01°C per minute, compared to 0.91°C per minute in stainless steel. The thermal conductivity of aluminium is around 205 W/m°C with a density of about 2.7 g/cm³, while stainless steel has a thermal conductivity of only 15–25 W/m°C and a density of approximately 7.8 g/cm³. The highest average solar radiation during the test was 424.1 W/m². The solar cooker was able to cook potatoes to a normal level in 48 minutes, from 14:26 to 15:13 on August 3, 2024, reaching a final temperature of 100.1°C, under the lowest average radiation of 216.22 W/m². In another test, 104 grams of potatoes were cooked in 35 minutes, with the temperature increasing at a rate of 1.62°C per minute in the aluminium container, reaching a final temperature of 103°C. In contrast, the stainless steel container had a rate of 1.31°C per minute and reached a final temperature of 91.3°C.The test also showed that battery voltage has a significant impact on cooking efficiency, as it affects the power needed for cooking materials, such as water.